Elderly-onset rheumatoid arthritis vs. polymyalgia rheumatica: Differences in pathogenesis - Wu, Jinzhi; Yang, Fan; Ma, Xinlei; Lin, Jin; Chen, Weiqian (Frontiers in Medicine, 2023)
Rheumatoid arthritis is a chronic autoimmune disease that mainly affects facet joints. Elderly-onset rheumatoid arthritis appears to exhibit symptoms similar to those of polymyalgia rheumatica, characterized by morning stiffness and pain in the shoulder and hip joints. Both diseases develop in the elderly, and sometimes it is challenging to distinguish them. Here, we compare the difference in the pathogenesis between elderly-onset rheumatoid arthritis and polymyalgia rheumatica to make assist with a clear differential diagnosis and early effective intervention.